Priority Directions of Providing Tax Benefits - Amanov , Akram Mirzaevich (Miasto Przyszłości, 2024)
Currently, further liberalization of the tax policy and reduction of the tax burden are important mainly to reduce taxation from the income of economic entities, to identify inefficient types of taxes, and to improve tax administration. The article describes the nature of tax benefits, the organization of tax services in providing them, and the priorities of tax services.